EFEKTIFITAS KEBIJAKAN KURSUS CALON PENGANTIN DALAM PENGUATAN KELUARGA MUDA (Studi Pada Kantor Urusan Agama Kecamatan Ratu Samban Kota Bengkulu) - Fitri, Rahmi (UIN Fatmawati Sukarno Bengkulu, 2018)
The study concluded that: first, the policy taken by the head of the KUA Kecamatan Ratu Samban suscatin services was related to schedule the execution of suscatin, providing a free service to any of the participants suscatin, implement the suscatin for 2 hours with priority material pertaining to marriage and households only. Second, the implementation of suscatin in KUA Kecamatan Ratu Samban held as much as 2 times in a week, namely on Thursday. Participants who follow suscatin at KUA Kecamatan Ratu Samban average each week 2 – 3 couples or 8 – 12 pairs per month. The material provided among others the procedures for marriage, wedding, Fiqh rules on marriage and the family, the rights and obligations of husband and wife and family concepts of sakinah is given by using the method of lecture and question and answer. The bride gives a varied response associated with the Government’s policy to hold suscatin to every bride. Third, the evaluation of the implementation of the suscatin in the Subdistrict of Ratu Samban KUA is already well underway in accordance with the tasks and functions primarily in the service of marriage guidance to society. Implementation of the suscatin Sub-district office KUA Ratu Samban quite effective and successful in adding to the knowledge and insight of the bride that will foster household. Suscatin be a posi- tive effort in provide knowledge to the prospective bride and groom. This is an attempt to prevent early on things which can disrupt home life in order not to divorce occurs